Correction to: Measuring treatment effect on psoriatic arthritis-related domains: insights from the SPIRIT-H2H study at weeks 24 and 52 (Clinical Rheumatology, (2021), 40, 12, (4943-4954), 10.1007/s10067-021-05891-5) - Behrens, Frank; Leage, Soyi Liu; Sapin, Christophe; El Baou, Celine; De La Torre, Inmaculada; Meszaros, Gabriella; Schett, Georg; Combe, Bernard; Van Den Bosch, Filip; Gossec, Laure (Clinical Rheumatology, 2021)
In the original published version of this article, the Figure 4 contained error. The line “ACR50 plus PASI100” has been presented incorrectly. The Figure 4 is now presented correctly. The original article has been corrected. (Figure presented.).
CRIS-Team Scopus Importer:2021-11-26